Morfologi Polen Dan Jenis Tumbuhan Yang Terdapat Pada Pollen Lebah Stingless Bees (Trigona spp.) Dari Pulau Nunukan, Kalimantan Utara - Dahlia, Dahlia; Syafrizal, Syafrizal; Hariani, Nova (BIOPROSPEK: Jurnal Ilmiah Biologi, 2019)
Stingless bees (Trigona spp.) are pollinators that play a role in pollination (pollination). Bees look for food on flowers because they accidentally bring pollen to their bodies and carry it as food ingredients. This research was conducted from January to March 2018, with the aim to find out the pollen morphology and the species of plant as feed sources of Stingless Bees (Trigona spp.). The method used in this study is the Acetolysis method. The most common form of pollen unit found in this research was monad unit form, there is only one unit of polyad and tetrad. While the most pollen form is the prolate spheroidal, the most common size of pollen is the medium size category. Aperture found consisted of inerturate, corporate, monocolpate, monosulcate, triporate, tricolpate, tricolor, trichotomosulcate, trichotomocolporate, trizono company, tetraporate and parasyncolpate. Sculpture consists of psilate, reticulate, perforate, echinate, scabrate, microreticulate and regulate. Observations from pollen morphological samples found 21 plant families with 28 different species which became the plant source of bee nectar.